The reduction of structural acoustic coupling in car bodies - Richards, T. L. (Cranfield University, 1982)
The nature of sound in cars is discussed in the light of previous experimental and theoretical work, and the major contributions to interior noise are identified. The acoustic field inside a vibrating structure is analysed theoretically in terms of the acoustic cavity modes and the structural modes, and it is shown that'reduction of structural-acoustic coupling could reduce the response for a wide variety of force inputs. Finite element analyses of prismatic acoustic cavities and two-dimensinal ring structures are described and these are combined in a simple theoretical model of ring-mode excitation of sound. By stiffening selected structural elements, the structural-acoustic coupling, and hence the acoustic response, are reduced.